ON THE CORRELATION OF BOTH VIBRATION AND CUTTING FORCES WITH THE ROUGHNESS OF THE WORKPIECE MACHINED SURFACE DURING TURNING - Talaat A. Elbenawy, Mohammed W. Alhazmi, Shadi M. Munshi (International Journal of Advanced Science and Technology, 2020)
Cutting forces and vibration of the machine tools was always subject of several works during the last few decades. In the present work, new correlation between the main cutting force and vibration with the undeformed chip cross‑section, during machining process of CNC turning machine, were established. Several types of workpiece materials, i. e. commercial aluminum, brass, bronze, stainless steel and carbon steel, were used during the machining process and both the principal cutting force and the vibrations at different locations were recorded. The roughness of the machined workpieces was also measured and attempts were conducted to analysis the collected data.